Curve fitting technique for optimal pulsewidth modulation (PWM) online control of a voltage source inverter (VSI) - Ahmad Azli, Naziha (2000)

(untitled)
A curve fitting technique to allow online computation of switching angles based on the optimal PWM switching strategies is presented. Detailed description of the curve fitting technique as applied to the optimal PWM switching angles trajectories for a VSI particularly for AC power conditioner or UPS applications is provided in this paper. This includes some analysis on the accuracy of the calculations based on the curve fitting technique compared with the exact solutions. The approach taken to actually implement this technique on a practical system is also highlighted